Optimization Analysis of Production Costs and Profits of Spicy Noodle Variants of Mie Ratu Situbondo UMKM Using The Branch and Bound Method - Aisyah, Sitti; Hasanah, Nur; Ida Fitriana Ambarsari (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to optimize production planning at UMKM Mie Ratu Situbondo, particularly for two main products, namely Mie Ratu Galak and Mie Ratu Ganas, in order to maximize daily profit and reduce inefficiencies in the use of raw materials. The background of this research is the production decision-making process that is still based on estimation, which often leads to suboptimal results and potential waste. The research method used is linear programming with the Simplex method, followed by the Branch and Bound method to obtain integer solutions. Data were collected through observation and interviews with the business owner over a period of more than seven days and were aggregated into daily average values. The analysis was carried out using MATLAB software. The results show that the optimal production combination is 63 portions of Mie Ratu Galak and 67 portions of Mie Ratu Ganas per day, resulting in a maximum profit of Rp1,434,000 per day. Compared to the previous condition, this result indicates an increase in profit and a more efficient allocation of resources. This study provides practical benefits for UMKM actors by offering a systematic and quantitative approach to production planning, which can support better managerial decision-making and improve business performance.